Patient experience and satisfaction with inpatient service : development of short form survey instrument measuring the core aspect of inpatient experience - Wong, E; Coulter, A; Hewitson, P; Cheung, A; Yam, C; Lu, S; Tam, W; Yeoh, E (Public Library of Science, 2015)
Patient experience reflects quality of care from the patients’ perspective; therefore, patients’ experiences are important data in the evaluation of the quality of health services. The development of an abbreviated, reliable and valid instrument for measuring inpatients’ experience would reflect the key aspect of inpatient care from patients’ perspective as well as facilitate quality improvement by cultivating patient engagement and allow the trends in patient satisfaction and experience to be measured regularly. The study developed a short-form inpatient instrument and tested its ability to capture a core set of inpatients’ experiences. The Hong Kong Inpatient Experience Questionnaire (HKIEQ) was established in 2010; it is an adaptation of the General Inpatient Questionnaire of the Care Quality Commission created by the Picker Institute in United Kingdom. This study used a consensus conference and a cross-sectional validation survey to create and validate a short-form of the Hong Kong Inpatient Experience Questionnaire (SF-HKIEQ). The short-form, the SF-HKIEQ, consisted of 18 items derived from the HKIEQ. The 18 items mainly covered relational aspects of care under four dimensions of the patient’s journey: hospital staff, patient care and treatment, information on leaving the hospital, and overall impression. The SF-HKIEQ had a high degree of face validity, construct validity and internal reliability. The validated SF-HKIEQ reflects the relevant core aspects of inpatients’ experience in a hospital setting. It provides a quick reference tool for quality improvement purposes and a platform that allows both healthcare staff and patients to monitor the quality of hospital care over time.